2022
DOI: 10.1111/rec.13702
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping of Pennisetum sinese with Lolium perenne improved phytoextraction of heavy metal from soil

Abstract: In order to find the optimum planting pattern for phytoremediation of metal‐accumulating plants in heavy metal‐contaminated soils, Pennisetum sinese and Lolium perenne were intercropped or monocultured, and the plant leaf physiological indexes as well as the heavy metal contents and accumulation of the two plants were determined. The contents, accumulation, and bioconcentration of Pb, Cd, Cu, and Zn in different parts of the two plants under the intercropping method were significantly (p < 0.05) higher than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…The decrease in soil pH was observed in all soil Cd treatments in intercropping. The ndings of our study align with previous research, which demonstrated that a decrease in soil pH leads to an increase in the bioavailability of Cd (Lian et al, 2022) and is the key reason for the greater root Cd uptake and higher Cd concentration in aboveground plant parts (Tsadilas et al, 2005;Zou et al, 2023). Bian et al (2021) found that intercropping bamboo and Sedum plumbizincicola led to an increase in biomass and a decrease in soil pH, which facilitated the removal of heavy metals from the soil.…”
Section: Intercropping Enhanced Plant Biomass By Modulating Photosynt...supporting
confidence: 89%
“…The decrease in soil pH was observed in all soil Cd treatments in intercropping. The ndings of our study align with previous research, which demonstrated that a decrease in soil pH leads to an increase in the bioavailability of Cd (Lian et al, 2022) and is the key reason for the greater root Cd uptake and higher Cd concentration in aboveground plant parts (Tsadilas et al, 2005;Zou et al, 2023). Bian et al (2021) found that intercropping bamboo and Sedum plumbizincicola led to an increase in biomass and a decrease in soil pH, which facilitated the removal of heavy metals from the soil.…”
Section: Intercropping Enhanced Plant Biomass By Modulating Photosynt...supporting
confidence: 89%
“…R. simsii and L. perenne showed potential in phytoextraction for soils contaminated with trace elements [ 52 , 53 ]. In the intercropping mode, the organic acids secreted by R. simsii roots may increase the bioavailability of trace elements in the soil, enhance the ability of R. simsii and L. perenne to accumulate trace elements, and promote the accumulation of L. perenne biomass [ 54 , 55 ]. This intercropping mode facilitated the transfer of trace elements in the soil to the vegetation, which, in turn, reduced the loss of trace elements from the riparian zone [ 9 ].…”
Section: Discussionmentioning
confidence: 99%